Gender norms, violence and adolescent girls' trajectories: Evidence from a field experiment in India - Alison Andrew; Sonya Krutikova; Gabriela Smarrelli; Hemlata Verma (Institute for Fiscal Studies (IFS), 2022)
Striking gender gaps persist in fundamental aspects of human welfare. In India, the setting of this paper, these gaps are particularly large. Interventions often target adolescent girls with the aim of empowering them to make choices that go against the status quo - to remain in school longer or marry later, for example. This approach may inadvertently expose girls, who are often marginalized within their communities, to new risks if it encourages them to violate prevailing gender norms. In this study, we design an experiment to compare the effectiveness of targeting only adolescent girls with an approach that additionally engages with the enforcers of gender norms in the wider community. We find that both arms of the trial led to a reduction in school dropout and early marriage. We see large improvements in girls' mental health but only in the arm which engages with the wider community. Improvements in mental health can be explained by community engagement causing gender norms to become more progressive and causing a reduction in the severity of sanctions that girls face for breaking norms. Both adolescent girls and their mothers perceived these shifts in norms and sanctions. Our results demonstrate that in settings where unequal outcomes are sustained through restrictive gender norms, change in the attitudes and behavior of the enforcers of these norms is critical for achieving meaningful improvements in women's well-being.
Keywords: 330; Girls; Adolescents; Social norm; Marriage; Education; Mental illness; Field research; India; Mädchen; Jugendliche; Soziale Norm; Ehe; Bildung; Psychische Krankheit; Feldforschung; Indien